Pemanfaatan Sistem Informasi Geografis terhadap kerusakan jalan di Kecamatan Medan Selayang - Dina Tri Septiningtiyas; Citra Utami; Tetra Oktaviani; Rifka Ananda (LPPM Politeknik Aceh Selatan, 2024)
Medan Selayang District is one of the sub-districts with the most populous activity center in Medan City where there is transportation infrastructure in the form of highways with various conditions, both roads with stable and unstable conditions so that they are vulnerable to roads damage. This study aims to map the level of potential road damage and analyze the level of potential road damage in Medan Selayang District using the Geographic Information System (GIS) application. The method used in this study is a data collection and data processing method using Quantum GIS. Data processing methods are in the form of georeferencing and digitization, parameter appreciation and overlap or overlay. The parameters used include slope, rainfall, soil type, traffic volume and the availability of drainage channels. The result of this study is a map of the potential level of roads damage in Medan Selayang sub-district with 3 categories of levels namely low damage along 4,714 Km (20.01%), moderate damage along 13,922 Km (59.12%) and high damage along 4,916 Km (20.87%). The distribution of potential road damage levels in Medan Selayang sub-district spreads for each category of damage levels